Beauty's Appeal Measure and Excess - Tymieniecka, Anna-Teresa.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Beauty fulfils human existence. As it registers in our aesthetic experience, beauty enhances nature’s enchantment around us and our inward experience lifting our soul toward moral elevation. Carried by creative imagination (Imaginatio Creatrix), beauty participates in the moulding of the forms of the intellective constitution of the mind in tandem with praxis and seeks deeper enigmas of the real in the labyrinth of the cosmos. Yet with the evolution of human development and in technological inventions, beauty, while suffusing all modalities of experience, seems to undergo transformations and expansion. Are there perduring norms and modalities of beauty or are we carried along blindly by human development? Is there a measure intrinsic to our human ontopoietic unfolding and the growth of human life that we may follow instead of the whim of fancy and excess? The present collection of art-explorations seeks the elemental ties of Human Condition. Together, the authors aim to answer the questions posed above. Papers by: Brian Grassom, Lawrence Kimmel, Gabriel Hindin, John Baldachino, Piero Trupia, Maria Golaszewska, Mariola Sulkowska, Valerie Reed, Max Statkiewicz, Victor Gerald Rivas, Robert D. Sweeney, Raymond J. Wilson III, Tsung-I Dow, Vladimir Marchenkov, Maciej Kaluza, Patricia Trutty-Coohill, Diane G. Scillia, Bruce Ross, James Werner, Elena Stylianou, Arthur Piper, Christopher Wallace, Matti Itkonen, Munir Beken, Andrew J. Svedlow.
Section I -- Eros/Kalon/Agathos -- The Beautiful Recollected -- Art After Beauty -- The Semantics of Beauty -- Section II -- The Aesthetics of Possibility -- Aesthetization of Aesthetic Values? -- Shattering Beauty -- From Perfect Beauty to a Conscious Life -- Von Hildebrands, Father and Son, and the Beautiful -- Section III -- Measure or Excess -- Measure and Excess -- Harmonious Balance -- The Dialectic of the Serious and the Ludic in Myth and Art -- Section IV -- The Theater of the Absurd and Reality -- Too Much Is Never Enough -- Minimalist Art -- Dances with Bears -- Section V -- The Re-Emergence of Beauty in Contemporary Technology -- Beauty and Truth in Science and Phenomenology -- Action and the Open Work -- Lived Words Re-Revisited -- Impenetrable Historiography and Value in Academic Music Composition -- Hermeneutic Phenomenology of Mark Rothko’s Painting.
Keywords: Aesthetics; Phenomenology .; Metaphysics; Ethics; Philosophy; Aesthetics; Phenomenology; Metaphysics; Ethics; Philosophy of Man